(untitled) - Skorman, Stuart (San Francisco, 2007)
Entrepreneur Stuart Skorman—the founder of Elephant Pharmacy, Hungryminds.com, Reel.com, and Empire Video—grew up in a retailing family in Ohio. He worked every kind of job, from cab driver to professional poker player to CEO. In this entertaining, personal account of his coming-of- age in the business world, Skorman gives an insider’s view of what it takes to start a business from the ground up. Stuart Skorman offers his hard-won lessons in business for any entrepreneur or small businessperson who wants to create a company that has a heart and soul. He reveals what he learned about marketing while working a stint as a rock band manager and bares his soul about his failure during the dot-com bubble. He describes in vivid terms the roller coaster ride of the entrepreneur in good times and bad and explains how to survive in today’s uncertain business environment.
Keywords: Businesspeople,New business enterprises,Doanh nhân; Biography,Tiểu sử; United States,United States,Hoa Kỳ